Ramp-up Journey of New Hires: Do strategic practices of software companies influence productivity? - Rastogi, Ayushi; Thummalapenta, Suresh; Zimmermann, Tom; Nagappan, Nachi; Czerwonka, Jacek (ISEC '17, 2017)
Software companies regularly recruit skilled and talented employees to meet evolving business requirements. Although companies expect early contributions, new hires often take several weeks to reach the same productivity level as existing employees. We refer to this transition of new hires from novices to experts as ramp-up journey. There can be various factors such as lack of technical skills or lack of familiarity with the process that influence the ramp-up journey of new hires. The goal of our work is to identify those factors and study their influence on the ramp-up journey. We expect the results from this study to help identify the need of various types of assistance to new hires to ramp-up faster. As a first step towards our goal, this paper explores the impact of two strategic practices, namely distributed development and internship on the ramp-up journey of new hires. Our results show that new hires in proximity to the core development team and new hires with prior internship experience perform better than others in the beginning. In the overall ramp-up journey, the effect of the two factors attenuates, yet nevertheless better compared to their counterparts. Product teams can use this information to pay special attention to non-interns and use better tools for distributed, cooperative work to help new hires ramp-up faster.